Die Staatenhaftung im Völkerrecht am Beispiel von informationstechnischen Gefährdungslagen - Karkaj, Sahar Moradi (Beiträge zum ausländischen öffentlichen Recht und Völkerrecht, 2021)
The necessity for state obligations to compensate transboundary harm becomes particularly evident in the virtual world. International law is predestined to address this issue but faces challenges due to the private character of information operations. Against this background, the author analyses the relationship between the established institute of state responsibility for internationally wrongful acts and the concept of state liability for non-prohibited dangerous activities. The contours of state liability are primarily derived from environmental law, WTO law, and investment protection. It is shown that state liability offers solutions to novel conflict situations. The findings can potentially be applied in various liability regimes.